How to Determine the Role of an Additive on the Length of Supramolecular Polymers? - Weyandt, Elisabeth; Mabesoone, Mathijs F. J.; de Windt, Lafayette N. J.; Meijer, E. W.; Palmans, Anja R. A.; Vantomme, Ghislaine (Organic Materials, 2020)
In polymer chemistry, modulation of sequence and control over chain length are routinely applied to alter and fine-tune the properties of covalent (co)polymers. For supramolecular polymers, the same principles underlying this control have not been fully elucidated up to this date. Particularly, rational control over molecular weight in dynamic supramolecular polymers is not trivial, especially when a cooperative mechanism is operative. We start this review by summarizing how molecular-weight control has been achieved in seminal examples in the field of supramolecular polymerizations. Following this, we propose to classify the avenues taken to control molecular weights in supramolecular polymerizations. We focus on dynamic cooperative supramolecular polymerization as this is the most challenging in terms of molecular weight control. We use a mass-balance equilibrium model to predict how the nature of the interaction of an additive B with the monomers and supramolecular polymers of component A affects the degree of aggregation and the degree of polymerization. We put forward a classification system that distinguishes between B acting as a chain capper, a sequestrator, a comonomer, or an intercalator. We also highlight the experimental methods applied to probe supramolecular polymerization processes, the type of information they provide in relation to molecular weight and degree of aggregation, and how this can be used to classify the role of B. The guidelines and classification delineated in this review to assess and control molecular weights in supramolecular polymers can serve to reevaluate exciting systems present in current literature and contribute to broaden the understanding of multicomponent systems.
Keywords: supramolecular polymers; chain-length control; chain capper